2000
DOI: 10.1121/1.428429
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-likelihood approach to strain imaging using ultrasound

Abstract: A maximum-likelihood (ML) strategy for strain estimation is presented as a framework for designing and evaluating bioelasticity imaging systems. Concepts from continuum mechanics, signal analysis, and acoustic scattering are combined to develop a mathematical model of the ultrasonic waveforms used to form strain images. The model includes three-dimensional (3-D) object motion described by affine transformations, Rayleigh scattering from random media, and 3-D system response functions. The likelihood function f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 54 publications
(79 reference statements)
0
49
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This method estimates local strains typically in the direction of compression by computing the gradient of shifts in echo arrival times after a quasistatic tissue compression. The echo shifts or tissue displacement are computed using a one-dimensional gated cross-correlation analysis of the pre-and post-compression radio-frequency (RF) signals, with overlapping windows to improve resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This method estimates local strains typically in the direction of compression by computing the gradient of shifts in echo arrival times after a quasistatic tissue compression. The echo shifts or tissue displacement are computed using a one-dimensional gated cross-correlation analysis of the pre-and post-compression radio-frequency (RF) signals, with overlapping windows to improve resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In this technique, local displacements are typically computed by applying a cross-correlation analysis to the pre-and postcompression ultrasonic radiofrequency (rf) echo signals. Strains are then estimated as the gradient of the displacements along the beam axis and displayed as a local strain image, referred to as an elastogram.…”
Section: Introductionmentioning
confidence: 99%
“…The sum of squared differences used as the similarity metric in our cost function is suitable if ultrasound noise can be modeled as additive Gaussian noise. However, ultrasound noise is not simply additive Gaussian and it has been shown that similarity metrics that model the noise process considering physics of ultrasound give more accurate results [68]. Performance of the 2D AM method for images that are not fully developed speckles (i.e have few scatterers per resolution cell) is also a subject of future work.…”
Section: Discussionmentioning
confidence: 99%